Si Juan tamad at ang mga bibingka Juan tamad and the rice cakes - Vibiesca, Renato C. (Lampara books, 2009)
"In our village, everyone is diligent--except Juan. The people say: "Juan is not to be emulated. Because from morning till night, he is covered with laziness." because he is extremely lazy, he is called "Juan tamad." One day, Juan is asked by his mother to sell in town a basket of delicious bibingka. Find out in this story what mischief Juan does to the bibingka and what value he learns from the experience."